Planejamento do ensino em salas multisseriadas na educação docampo de Paragominas - PA - BARROS, Jesias Pereira (2022)
This master thesis aimed to investigate the construction process of teacher’s planning in multigrade classes from 1st to 5th grade in rural schools in the city of Paragominas, Pará. It points out the challenges faced every day in the classroom, the transgression of the paradigms established in the school curriculum through the practice and knowledge materialized by the teachers of this territory. The research corroborates how the planning of educators who work in multigrade classes has the purpose of understanding the learning developed in peasant education and valuing this educational context. It was based on evidencing the teaching work, pointing out this teaching modality as one of the most important Amazonian collectives to be debated in the current scenario of Para and Brazilian Amazonian education. In order to better understand this ownership relationship with the theme, we used references such as; Rocha & Hage (2015); Santos (2016); Caldart (2020); Arroyo; Caldart; Molina (2009); Freire (1979), among other authors who contributed significantly to the understanding and discussion that mediated the construction of this work. Methodologically, the production of knowledge was analyzed through the reading of books, scientific articles, dissertations, concerning Field Education and multigrade classes, as well as the challenges for the construction of various plans or the ways found to condense the various lesson plans found as a solution by teachers. To collect the data, semi-structured interviews were used and questionnaires were applied using Google forms. Twelve teachers, three coordinators and one former Superintendent of the Department of Field Education participated in this research. The participants analyzed the educational arrangements created by the educators to teach in multigrade classes, dialoguing with local knowledge. During the research, visits were made to four multigrade schools in the municipality belonging to the southeastern mesoregion of Amazônia Paraense, for the construction of the documentary entitled Narratives of the multigrade in Paragominas - the final product of this dissertation. The dissertation is organized in six axes: The memory of the done and the report of the current, Pedagogical planning in the multigrade in the field education; The materiality of the origin of the field education and the multigrade; The multigrade in the context of the Brazilian Amazonian education; The continued formation of teachers: and the social function of the field school; The pedagogical planning of educators before and during the pandemic; Results and discussions of data analysis and interpretation. The results showed that the interviewed teachers feel the need to build the planning in an interdisciplinary way andthat they recognize the difficulties for the elaboration of lesson plans, which dialogue among themselves with the other areas of knowledge and demonstrated how much it is necessary to establish guidelines for the adequate or even reasonable performance of the work with multigrade/multigrade in the countryside.